2021
DOI: 10.1002/elsa.202100089
|View full text |Cite
|
Sign up to set email alerts
|

In vitro electrochemical assays for vascular cells and organs

Abstract: Vascular form vascular organs and the walls of blood vessels play a crucial role in transporting nutritive compounds and drugs. Vascular cells also release factors required to maintain the homeostasis of the organs. Since cancer cells travel from tumors to secondary sites during metastasis through the vasculature, it is important to investigate the interactions of vascular and cancer cells. In vitro vascular models, including endothelial cell monolayers, tubular structures in three‐dimensional culture scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Conventional models have been evaluated using immunostaining and gene analysis, which are endpoint analyses. By contrast, electrochemical measurements have been widely employed for cell analysis , because of their advantages such as minimal invasiveness and facilitation of real-time analysis. Recently, a microfluidic device with an electrode was developed and evaluated through different electrochemical measurements, including transepithelial electrical resistance measurements. , In particular, vascular models have been extensively studied, and various devices with electrodes have been proposed for the real-time evaluation of cell functions.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional models have been evaluated using immunostaining and gene analysis, which are endpoint analyses. By contrast, electrochemical measurements have been widely employed for cell analysis , because of their advantages such as minimal invasiveness and facilitation of real-time analysis. Recently, a microfluidic device with an electrode was developed and evaluated through different electrochemical measurements, including transepithelial electrical resistance measurements. , In particular, vascular models have been extensively studied, and various devices with electrodes have been proposed for the real-time evaluation of cell functions.…”
Section: Introductionmentioning
confidence: 99%
“…Utagawa et al have reported a review on the application of in vitro electrochemical assays on vascular cells (VCs) and organs. 18 They have categorized 7 strategies of electrochemical structures for VCs and models that mainly involve HUVECs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, microscopic methods, such as fluorescence imaging, can visualize biomarkers via immunostaining [7]. In electrochemical analyses, electrochemical probe and electrode-array devices have been applied to vascular cells and tissues to evaluate their various functions, such as respiration activity and the production of nitric oxides, gene expression, cellular permeability, and cell barrier functions [8]. Transepithelial/endothelial electrical resistance (TEER) measurement is extensively used to monitor and examine integrity of the endothelial cell barrier.…”
Section: Introductionmentioning
confidence: 99%